Effects of melatonin on Leydig cells in pinealectomized rat: an immunohistochemical study - Kus, I; Akpolat, N; Özen, OA; Songur, A; Kavakli, A; Sarsilmaz, M (Elsevier Gmbh, 2002)
We have investigated imnunohistochemically the effects of melatonin on Leydig cells in rat. Three groups of Wistar rats were used. Rats in group I and II were sham-pinealectomized (control) and pinealectomized, respectively, whereas rats in group III were pinealectomized and injected daily with melatonin for 2 months. At the end of the experiment, all animals were killed by decapitation and blood samples were obtained. Serum testosterone levels were determined with the use of a chemiluminescent enzyme immunoassay. Testicular tissue was collected and processed for semiquantitative evaluation of immunohistochemical testosterone staining. Intensity of immunostaining was determined on a scale between 0 (no staining) and 5 (heavy staining). In pinealectomized rats, serum testosterone levels were significantly increased as compared to sham-pinealectomized rats. Daily administration of melatonin after pinealectomy resulted in significant decreased serum testosterone levels as compared to levels in control and pinealectomized rats. Immunostaining of testosterone was moderate (3+) in sham-pinealectomized rats, heavy (5+) in pinealectomized rats and low (1+) in pinealectomized rats that were treated with melatonin, respectively. The results of our study indicate that pinealectomy induces increased testosterone secretion in Leydig cells and this increased secretion can be prevented by administration of melatonin.
Keywords: immunohistochemistry; Leydig cell; melatonin; pinealectomy; rat; testosterone